2005
DOI: 10.1111/j.1478-3231.2005.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide in previously untreated autoimmune hepatitis

Abstract: Budesonide monotherapy was effective in the induction of remission and well tolerated in treatment naïve patients with AIH. It should be further evaluated in prospective controlled trials and should be compared to predniso(lo)ne both in monotherapy and in combination with azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 25 publications
0
43
0
1
Order By: Relevance
“…Preliminary studies in patients with mild disease have suggested that it is useful in selected patients as a frontline treatment, [111][112][113] and these small reports have justified the performance of a randomised clinical trial. The European trial compared the combination regimen of budesonide (3 mg thrice daily) and azathioprine (1-2 mg/kg daily) with that of prednisone (40 mg daily, tapered to 10 mg daily) and azathioprine (1-2 mg/kg daily) in 203 treatment-naïve patients with autoimmune hepatitis.…”
Section: -110mentioning
confidence: 99%
“…Preliminary studies in patients with mild disease have suggested that it is useful in selected patients as a frontline treatment, [111][112][113] and these small reports have justified the performance of a randomised clinical trial. The European trial compared the combination regimen of budesonide (3 mg thrice daily) and azathioprine (1-2 mg/kg daily) with that of prednisone (40 mg daily, tapered to 10 mg daily) and azathioprine (1-2 mg/kg daily) in 203 treatment-naïve patients with autoimmune hepatitis.…”
Section: -110mentioning
confidence: 99%
“…A potential advantage over prednisolone is the theoretical ability to achieve high local tissue levels without systemic adverse effects. Budesonide is effective in both inducing and maintaining remission [114], although there is currently no good evidence that budesonide provides a benefit over prednisolone and care must be taken when using it in patients with cirrhosis in whom shunting may reduce hepatic first pass metabolism [115,116].…”
Section: Treatment Failure and Alternative Therapies For Aihmentioning
confidence: 99%
“…However, it cannot be expected that budesonide treatment will overcome treatment failure following conventional combination therapy with prednisone and azathioprine. The main advantage of a topical steroid such as budesonide might be the replacement of conventional steroids in long-term maintenance therapy in order to reduce systemic steroid-specific side effects [7,15]. However, such a benefit should only be observed in noncirrhotic patients in the absence of portosystemic shunting.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 99%